Lithium ion conduction and ion-polymer interaction in PVdF-HFP based gel polymer electrolytes - Isa, K.B.M.; Osman, Z.; Arof, Abdul Kariem; Othman, L.; Zainol, N.H.; Samin, S.M.; Chong, W.G.; Kamarulzaman, N. (Elsevier, 2014)
The GPE films consisting of PVdF-HFP as host polymer, LiCF3SO3 as dopant salt and the mixture of EC and PC as plasticizing solvent were prepared by the solution casting technique. The ionic conductivity at room temperature and the conductivity-temperature dependence were determined by a.c impedance spectroscopy. The result of conductivity versus temperature obeys the VTF rule. The increase in the conductivity is due to the increase in the number of mobile charge carriers and the decrease in ion pairs and ion aggregates as revealed by the FTIR spectra. These results are consistent with its morphological properties. (C) 2014 Elsevier B.V. All rights reserved.